2006
DOI: 10.5213/inj.1630380.190
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical OnabotulinumtoxinA Injection for Overactive Orthotopic Ileal Neobladder: Feasibility and Efficacy

Abstract: The efficacy of intravesical onabotulinumtoxinA (BTXA) in the treatment of overactive bladder (OAB) has been well documented. The use of BTXA injection in orthotopic neobladders is yet to be studied. We present 4 cases of patients injected with intravesical BTXA for overactive orthotopic ileal neobladder. We recorded patient demographics, presenting and follow-up symptoms, urodynamic profiles, and Patient Global Impression of Improvement (PGI-I) scores. The 4 patients reported varying degrees of subjective imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have described the presence of neobladder over-activity and the association with nocturnal incontinence and urge incontinence [ 19 , 20 ]. A recent study has shown the efficacy of intravesical botulinum toxin injection in the treatment of patients with neobladder over-activity and urinary incontinence [ 21 ]. In our urodynamic evaluation, we could not definitively define neobladder over-activity due to various forms of intraluminal pressure change and urodynamic artifact.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the presence of neobladder over-activity and the association with nocturnal incontinence and urge incontinence [ 19 , 20 ]. A recent study has shown the efficacy of intravesical botulinum toxin injection in the treatment of patients with neobladder over-activity and urinary incontinence [ 21 ]. In our urodynamic evaluation, we could not definitively define neobladder over-activity due to various forms of intraluminal pressure change and urodynamic artifact.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence suggests that superior efficacy was obtained after combining injection into the detrusor and bladder trigone compared with intradetrusor injection alone [22]. A recent study carried out by Hoag et al [23] showed that, intravesical onabotulinumtoxinA injection is feasible treatment for overactive bladder in orthotopic neobladders. Further studies are needed to determine whether single detrusor injection or combination with trigone injections increases onabotulinumtoxinA efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…There are clear data showing significant urodynamic and subjective improvements after administration of BTX-A injections in the neurogenic population with either 200 or 300 units. [12,13] Long-term data show that the mean duration of efficacy of intravesical BTX-A is 6-9 months. [12] Our cohort of patients appeared to have longer efficacy with an average repeat injection time of 10.5 months (range 2-42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been a case series reporting the use of BTX-A (100-200 units) in four patients with overactive orthotopic neobladder. [13] The authors utilized a minimal depth of needle penetration into the neobladder mucosa (2-3 mm) to decrease the risk of bowel injury or perforation. In this study, there were no significant adverse events with injection of BTX-A into a bowel segment.…”
Section: Discussionmentioning
confidence: 99%